Pelatihan Penggunaan Aplikasi Keuangan untuk Optimalisasi Penjualan guna Scale Up Bisnis UMKM - Shiwi Angelica Cindiyasari; Berlintina Permatasari; Almira Devita Putri; Larasati Ahluwalia; Defia Riski Anggarini; Elvina Septiani; Nurul Sakinah (Journal of Engineering and Information Technology for Community Service, 2023)
Micro, Small and Medium Enterprises (MSMEs) play an important role in the economic development of a country, where they can contribute to economic growth, absorb employment through the creation of new jobs, and distribute the results of development. Therefore, there is a need to improve the quality of resources in managing and developing MSMEs in order to improve Indonesia's economy. Universitas Teknokrat Indonesia conducted Community Service activities by providing training on financial application usage to increase sales and develop MSME businesses. During the visit, it was found that MSME practitioners had only been recording their finances manually, often forgetting to record sales and finances. This became an opportunity to add knowledge to business practitioners about the use of technology to develop their business. After the training, there was a significant increase in knowledge between before and after the training. This training is expected to help MSME practitioners manage their business finances effectively and efficiently so that they can develop their business on a larger scale.